Postgraduate student experience at an emerging market higher education institution - Wait, M.; Stiehler-Mulder, B. (South African Journal of Higher Education, 2024)
A constructive learning experience for postgraduate students is important for higher educational institutions, particularly in emerging markets such as South Africa. The context of the student and supervisor relationship, operating in an intensive service delivery system, is also vitally important in this context, in order to secure a positive and successful learning outcome for the student. This study’s aim is to evaluate postgraduate students’ learning experience in an intensive higher educational service delivery system. It places the student at the center of a service design and relationship marketing approach, and highlights several areas of exploration. The study adopted a qualitative approach. Several online interviews were conducted with masters and doctoral students. The data was collected online and analysed using inductive content analysis. The main results indicate that, overall, the students’ experience and emotions were positive, but that the lecturer, as internal stakeholder in the service system, should receive more support. The contributions of this study are in the practical implementation of an improved service design experience, and the elimination of possible service gaps, to secure customer loyalty and effective service delivery.